A stronger role for the European Parliament in the design of the EU's investment policy as a legitimacy safeguard - Catharine Titi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2017)
Since the Treaty of Lisbon, the European Commission has designed an innovative investment policy, leaving in the shadows another powerful actor. And yet, in the post-Lisbon era, the European Parliament enjoys extensive powers in the formulation of the EU's investment policy.
Keywords: 330